2007
DOI: 10.1016/j.bbamem.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Metal contaminants promote degradation of lipid/DNA complexes during lyophilization

Abstract: Oxidation reactions represent an important degradation pathway of nucleic acid-based pharmaceuticals. To evaluate the role of metal contamination and chelating agents in the formation of reactive oxygen species (ROS) during lyophilization, ROS generation and the stability of lipid/DNA complexes were investigated. Trehalose-containing formulations were lyophilized with different levels of transition metals. ROS generation was examined by adding proxyl fluorescamine to the formulations prior to freeze-drying. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…In addition, it may suggest an alternative mode of Fe 3+ entry into the periplasm in which the Fe 3+ /pyrophosphate complex tears off slowly under an aerobic condition in the presence of a reducing power from an unknown resource at a physiological temperature. Note that chelated iron in the presence of oxygen and a reducing agent can lead to repetitive cleavage of macromolecules such as DNA (Enright et al, 1992;Molina and Anchordoquy, 2007) and that an Fe 3+ /ADP chelate complex can cause lipid peroxidation of a mitochondrial lipid in a reducing agent-dependent manner in Eucaryotes (Takeshige et al, 1980). However, it is also true that Fe 3+ -mediated bacterial cell killing of the pmrA mutant can still occur even under anaerobic conditions in a growth-dependent manner (Chamnongpol et al, 2002).…”
Section: +mentioning
confidence: 99%
“…In addition, it may suggest an alternative mode of Fe 3+ entry into the periplasm in which the Fe 3+ /pyrophosphate complex tears off slowly under an aerobic condition in the presence of a reducing power from an unknown resource at a physiological temperature. Note that chelated iron in the presence of oxygen and a reducing agent can lead to repetitive cleavage of macromolecules such as DNA (Enright et al, 1992;Molina and Anchordoquy, 2007) and that an Fe 3+ /ADP chelate complex can cause lipid peroxidation of a mitochondrial lipid in a reducing agent-dependent manner in Eucaryotes (Takeshige et al, 1980). However, it is also true that Fe 3+ -mediated bacterial cell killing of the pmrA mutant can still occur even under anaerobic conditions in a growth-dependent manner (Chamnongpol et al, 2002).…”
Section: +mentioning
confidence: 99%
“…However, DNA must resist the freezing and drying stresses encountered during processing before stability can be addressed. In this respect, it has been demonstrated that the addition of disaccharides, such as sucrose and trehalose, are beneficial to prevent loss of SC DNA during lyophilization [55,56,82,91,96,113,115,121,178,179].…”
Section: Stability Of Dried Plasmid Dnamentioning
confidence: 99%
“…Considering that biomolecules are immobilized in a glassy-excipient phase where reactions requiring positional specificity would be considerably inhibited in the dried state [127], our recent findings show that degradation can still occur at significant rates despite maintenance of a glassy phase (e.g., in trehalose). In fact, our validated fluorescent-based method [115] has been used consistently to detect the formation of ROS in lyophilized naked DNA, lipid alone, as well as lipid/DNA complexes, and demonstrated that ROS are still active in the solid state [115,178,179,183]. Furthermore, our findings suggest that trace metal contamination (Cu ) is a prominent factor affecting the stability of these biomolecules, particularly when an unsaturated lipid is present in the formulation composition (e.g., dried lipid/DNA complexes, as described in corresponding section of this chapter) [179,183].…”
Section: Stability Of Dried Plasmid Dnamentioning
confidence: 99%
See 2 more Smart Citations